THE INFLUENCE OF BRAND AWARENESS AND BRAND ASSOCIATION ON NETFLIX BRAND EQUITY THROUGH BRAND LOYALTY - Felicia Natalie; Rini Anggriani; Lady Faerrosa (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Abstract       The increasingly fierce competitive environment between companies and the challenges faced by Video On Demand services, especially in this study, namely Netflix, the company needs to strengthen brand equity so that the brand owned becomes superior to competitors.This study aims to determine and analyze the influence of brand awareness and brand association on Netflix brand equity through brand loyalty. The type of research conducted is quantitative descriptive with a causal approach, sampling techniques using purposive sampling and obtained a sample of 170 respondents. Analysis method using SEM with Amos 24.0 Analysis tool.The results showed that brand awareness has no effect on brand equity, brand association affects brand equity, brand loyalty affects brand equity, brand awareness affects brand loyalty, brand association has no effect on brand loyalty. Also, brand loyalty is able to mediate the influence of brand awareness on brand equity. However, brand loyalty is not able to mediate the influence of brand association on brand equity. Based on the results of research that has been done, it can be concluded that the importance of building a strong and positive brand association and increasing brand loyalty to strengthen Netflix's brand equity